You try to do your best: Teacher reflections and subject constructs in lower secondary education for adults - Anundsen, Lene (Acta Didactica Norden, 2023)
The study examines how three Norwegian teachers interpret or construct different versions of the school subject Norwegian within a specific teaching context: primary education for adult immigrants. These adult pupils have immigrated to Norway quite recently and are still in the process of learning the language. However, the current curriculum and the examination arrangements are the same as for the ordinary primary school, even if new curricula, more adapted to adult second-language users, are planned for implementation in the course of 2024. The study is primarily based on verbal data from semi-structured research interviews with the three teachers of Norwegian. Based on the teachers’ own descriptions, the contextual introductory part of the analysis reveals a number of challenges linked to their teaching tasks. The next part investigates how the teachers adapt the subject through their own subject constructs – personal conceptions of the Norwegian subject. The analysis shows, among other things, that literary texts are used and legitimized differently in the three subject constructs. The final part of the study discusses how the challenges identified in the analysis are addressed in the upcoming preliminary curriculum and argues for an approach in which the participants’ multilingual literacy and background experiences are systematically used to inform and improve teaching.